ADDITIVE AND NON-ADDITIVE GENE EFFECTS FOR QUANTITATIVE TRAITS THROUGH LINE X TESTER ANALYSIS IN MULBERRY SILKWORM - D. JAMUNA; G. SUBRAMANYA (The Bioscan, 2010)
Combining ability effects were studied for thirteen quantitative parameters in silkworm Bombyx mori through line x tester mating design. Three evolved multivoltine lines (MU1, MU11, MU303) and one popular multivoltine race Pure Mysore were involved in the study and identified as females (lines) and two commercially popular bivoltine breeds (CSR2 and NB4 D2 ) along with two evolved bivoltine breeds of Mysore University (MG408 and MU854) were chosen as males (testers) and a total of sixteen hybrids were derived. All the twenty-four genotypes were reared under standard rearing conditions. Among the lines, MU1 and MU11 and the two testers MG408 and NB4 D2 exhibited significant +ve general combining ability (GCA) effects for most of the traits understudy indicating the importance of additive gene action. Out of sixteen hybrids MU1 x MG408, MU11 x CSR2, MU303 x MU854 and PM x NB4 D2 were found to be the best hybrid combinations with significant specific combining ability (SCA) effects confirming the importance of non-additive gene action. The ANOVA results based on the pooled data for thirteen economic traits revealed significant interaction among the testers, lines and between lines x testers. The developments of new hybrids through line x tester analysis are here in discussed.